Fly Ash Slurry Transportation: Indian Scenario - Md Aquil Ahmad; Zeeshan Ali; Md Emamul Haque (Waste Technology, 2014)
Fly ash produced in pulverized form are menace to transport due to its powder form. Converting it to slurry form as the physical state change makes it technically viable to move from one place to other convenience to transport. In this paper we envisage the contemporary scenario of transportation of flyash including special focus on trouble related to flyash transportation whether to use in backfilling of mines or open area disposal the transport of these fine particle ash is an issue. Further suggestions and improvement for working of fly ash